Evaluasi Pendidikan dalam Perspektif Filsafat Pendidikan Islam - Yusril Muhammad Nur; Zainal Arifin Ahmad (CV. Biha Cendekia, 2025)
Evaluation is a crucial aspect of education as it serves to measure the extent to which learning objectives are achieved. However, many educators still lack a comprehensive understanding of educational evaluation, which results in less optimal implementation. This study aims to examine educational evaluation from the perspective of Islamic educational philosophy, particularly in assessing students’ abilities as well as recognizing the broader role of evaluation in social life. The research employed a library research method with a descriptive qualitative approach, analyzing relevant literature such as books, articles, and scientific works. The findings indicate that educational evaluation encompasses several key aspects, including the interrelationship between measurement, assessment, and evaluation; the objectives and principles of educational evaluation; and various types of evaluation, such as formative, summative, placement, and diagnostic. From a philosophical standpoint ontology, epistemology, and axiology educational evaluation not only functions to measure learning outcomes but also serves as a means to improve processes, enhance quality, and reinforce the values of Islamic education.